Chemical Evaluation of the Nutritive Value of Pentaclethra macrophylla benth (African Oil Bean) Seeds - Alinnor, I.J.; Oze, R. (Pakistan Journal of Nutrition, 2011)
Pentaclethra macrophylla benth (African oil bean) seeds were analyzed for their nutritive values. The result showed that Pentaclethra macrophylla seeds have moisture content 11.87%, ash content 2.95%, crude fat content 46.95%, crude protein content 20.95%, crude fibre content 2.50%, carbohydrate content 14.79%, available energy 2344.56 kJ. The mineral content of the analyzed samples showed that Pentaclethra macrophylla seeds were rich in iron of value 140.97 mg/100 g. The analysis indicates that potassium is the most abundant mineral. The high Ca/P ratio indicates that Pentaclethra macrophylla is a very good food source.